2018
DOI: 10.1007/164_2017_89
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Neuronal, and Behavioral Effects of Ethanol and Nicotine Interactions

Abstract: Ethanol and nicotine can modulate the activity of several neurotransmitter systems and signalling pathways. Interactions between ethanol and nicotine can also occur via common molecular targets including nicotinic acetylcholine receptors (nAChRs). These effects can induce molecular and synaptic adaptations that over time, are consolidated in brain circuits that reinforce drug-seeking behavior, contribute to the development of withdrawal symptoms during abstinence and increase the susceptibility to relapse. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 196 publications
0
12
0
Order By: Relevance
“…Since possible direct interactions between EtOH and nACHRs have been reported [29,30], we verified in drug-naïve animals that the EtOH addiction-like phenotypes observed in α5SNP rats were not due to differences in EtOH metabolism. Blood EtOH concentrations were similar between groups at all time-points following a 2 g/kg EtOH injection (Fig.…”
Section: Etoh Metabolism Locomotor Activity and Anxiety Levels In α5mentioning
confidence: 54%
See 2 more Smart Citations
“…Since possible direct interactions between EtOH and nACHRs have been reported [29,30], we verified in drug-naïve animals that the EtOH addiction-like phenotypes observed in α5SNP rats were not due to differences in EtOH metabolism. Blood EtOH concentrations were similar between groups at all time-points following a 2 g/kg EtOH injection (Fig.…”
Section: Etoh Metabolism Locomotor Activity and Anxiety Levels In α5mentioning
confidence: 54%
“…Both alcohol and nicotine can modulate signalling pathways implicated in addiction through both distinct and common molecular targets. In fact, EtOH has been shown to act as an allosteric modulator of nAChRs and suggested to alter the balance between activation and desensitization of nAChRs caused by nicotine [30]. Previous studies reported no alterations in EtOH intake in α5 knock-out (KO) mice in a drinkingin-the-dark paradigm [38,40], although EtOH intake was actually decreased in these mice, in a similar paradigm, after a restraint stress [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLT and alcohol are both psychoactive substances containing nicotine and ethanol molecules, respectively [27], and their synergistic interactive effects potentiate physical and psychological pleasure [28]. Therefore, polyconsumption of both tobacco and alcohol was not surprising [29].…”
Section: Co-use Of Alcoholmentioning
confidence: 99%
“…SLT and alcohol are both psychoactive substances containing nicotine and ethanol molecules, respectively [27] and their synergistic interactive effects potentiate physical and psychological pleasure [28]. That explains why polyconsumption consisting in combining tobacco and alcohol was not surprising [29].…”
Section: Co-use Of Alcoholmentioning
confidence: 99%